2022
DOI: 10.1111/2041-210x.13854
|View full text |Cite
|
Sign up to set email alerts
|

River networks: An analysis of simulating algorithms and graph metrics used to quantify topology

Abstract: 1. River networks are frequently simulated for use in the development and testing of ecological theory. Currently, two main algorithms are used, stochastic branching networks (SBNs) and optimal channel networks (OCNs). The topology of these simulated networks and 'real' rivers is often quantified using graph theoretic metrics; however, to date, there has not been a comprehensive analysis of how these algorithms compare regarding graph theoretic metrics, or an analysis of metric redundancy and variability acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 70 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…While we found that BBTs are highly inaccurate in reproducing ecological metrics of real river networks and should be therefore discarded altogether in future modelling applications, RBNs show a certain degree of similarity with OCNs and real river networks in this respect; moreover, RBNs (as is the case for any random tree 61 ) satisfy Horton's laws on bifurcation and length ratios. A relevant advantage of RBNs over OCNs is that their generation algorithm is at least one order of magnitude faster 49 . Therefore, we acknowledge that RBNs could be considered as a suitable surrogate for real river networks as null models in cases where a large number of network replicates is required.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While we found that BBTs are highly inaccurate in reproducing ecological metrics of real river networks and should be therefore discarded altogether in future modelling applications, RBNs show a certain degree of similarity with OCNs and real river networks in this respect; moreover, RBNs (as is the case for any random tree 61 ) satisfy Horton's laws on bifurcation and length ratios. A relevant advantage of RBNs over OCNs is that their generation algorithm is at least one order of magnitude faster 49 . Therefore, we acknowledge that RBNs could be considered as a suitable surrogate for real river networks as null models in cases where a large number of network replicates is required.…”
Section: Resultsmentioning
confidence: 99%
“…While some studies acknowledged possible shortcomings of certain network approximations 25 , the effects of inadequate network analogues on the ecological dynamics analyzed have not been systematically addressed (but see ref. 49 ). Specifically, a first group of studies 25,33,34,36,37,43,45,50 modelled river networks as trees where all paths from the tree root to the source nodes (see Supplementary Note 1) have equal length; borrowing an analogy from computer science, these will hereafter be defined balanced binary trees (BBTs -Fig.…”
mentioning
confidence: 99%
“…We constructed dendritic networks consisting of 50 patches using the optimal channel network (OCN) algorithm (Rinaldo et al, 2014). OCNs are oriented spanning trees (built on rectangular lattices) that reproduce some of the features characteristic of real river networks (Carraro & Altermatt, 2022; Lee et al, 2022; Rinaldo et al, 2014; Rodriguez‐Iturbe et al, 2009). The algorithm starts with a feasible network configuration imposed on a lattice landscape, and the OCNs are obtained by minimization of a function representing the total energy dissipated by water flowing through the network spanning the lattice.…”
Section: Methodsmentioning
confidence: 99%
“…Analyzing Graph Structure. The study of different graph types and their structures has been performed in [29], [57], [58], [59], [12] that present different topological metrics and tools to analyze the differences between different graph types.…”
Section: Impacts Of Creating Datasets On Progressing Researchmentioning
confidence: 99%